Curcuma siamensis (Zingiberaceae, Zingibereae), a new species of Curcuma subgen. Ecomatae from Southeastern Thailand: Curcuma siamensis (Zingiberaceae: Zingibereae), a new species of Curcuma subgen. Ecomatae from Southeastern Thailand - Piyaporn Saensouk; THAWATPHONG BOONMA; SURAPON SAENSOUK (Society for Indonesian Biodiversity, 2021)
Abstract. Saensouk P, Boonma T, Saensouk S. 2021. Curcuma siamensis (Zingiberaceae, Zingibereae), a new species of Curcuma subgen. Ecomatae from Southeastern Thailand. Biodiversitas 22: 5239-5246. Curcuma siamensis Saensouk & Boonma sp. nov. (Zingiberaceae: Zingibereae) belonging to the genus Curcuma subgenus Ecomatae, as herein described and illustrated discovered in Chachoengsao Province, Southeastern Thailand during our exploration of Zingiberaceae family in Thailand and in preparation for the revision of the genus Curcuma for the Flora of Thailand project. It is similar to Curcuma rangsimae Boonma & Saensouk in having terminal inflorescences between the leaf-sheaths, emerging at the basal of the pseudo-stem, lacking coma bract, yellow flowers, presence of epigynous glands, and anther spurs make this plant most similar to, which are also distributed in this nearby area too. But differ in having leaves narrowly elliptic, narrower and shorter in size 18–36 × 6–8.5 cm, upper midrib reddish; thyrse shorter and smaller (5–6.5 cm long, 4–5 cm in diam.); peduncle glabrous; bracts per inflorescence 10–15 in number, fused almost only at base; corolla lobes white, longer and narrower 17–18.3 × 6–7.8 mm; staminodes uniquely obovate-rhombic; labellum ovate-trullate; filament 4.4–4.5 mm long; anther longer c. 8 mm long, spurs pointing outward in front view, with anther crest apex retuse (vs. C. rangsimae having leaves narrowly elliptic to oblanceolate, 40–70 × 12–20 cm, upper midrib green; thyrse 12–20 cm long, 7.8–9.5 cm in diam.; peduncle pilose; 25–48 in number, connate 1/4 to 1/3 at base; corolla lobes light pale yellow, 15–17 × 9–12 mm; staminodes asymmetrical trullate–ovate; labellum ovate; filament 6–7 mm long; anther 6.3–6.9 mm long, spurs pointing downward in from view, with anther crest apex rounded). Based on the results of the morphological comparison and examination of all allied species in the same genus were found to be inconsistent with any species, especially in the subgenus Ecomatae. A comprehensive description, illustration, photographs, ecology, etymology, distribution and a revised key to 21species of Curcuma subgenus Ecomatae in Thailand are provided.